Pericles VR: towards pedagogical innovation through gamified adaptation of classic literature - Rall, Hannes (2024)
Our paper seeks to investigate how mediation using emerging technologies can increase student engagement within the context of teaching English Literature in Singapore. Through a discussion of our ongoing project to create an adaptation of Shakespeare’s Pericles, Prince of Tyre as an animated game in virtual reality, we focus upon the interdependencies between narrative content, style of visualization and interactive engagement to demonstrate the potential of fully immersive media in an educational context. Pericles is one of Shakespeare’s lesser-known plays: in five acts, it tells the dramatic story of a family separated at sea and reunited by fate. Our findings will highlight the opportunities that works of Shakespeare that fall outside the group of texts commonly studied offer for innovation within the classroom, as well as the benefits of taking a practice-led approach to research that draws together Shakespeare scholars, artists, researchers, and technical developers to adopt a playful yet meaningful approach towards educating secondary-level students. Most importantly, however, we will focus on demonstrating how our adaptation facilitates conclusions regarding employing animated immersive media for novel ways of teaching “boring”, complex, canonical literary texts. We suggest our adaptation prompts a reconsideration of means of student engagement for classical literature in general, and Shakespeare’s work in particular.